SOCIAL CONNECTEDNESS, GRATITUDE AND DEMOGRAPHIC VARIABLES ASPREDICTORS OF TEACHERS' PERCEPTIONS OF ORGANIZATIONALCYNICISM - Alanoğlu, Müslim; Karabatak, Songül (My University, 2021)
This study aimed to test the predictive power of teachers’ social connectedness and gratitude levels and their demographic characteristics to predict their organizational cynicism perception. The study was designed in a relational survey model. 304 teachers were reachedsampled from the population through the snowball sampling method. Data were collected using the Organizational Cynicism Scale, Social Connectedness Scale and, Gratitude Scale.Correlation analysis and hierarchical regression were performed during the analysis. According to correlation analysis results, there were moderate and negative associations between organizational cynicism and social connectedness and gratitude, low and negative association between organizational cynicism and gender, and low and positive associations between organizational cynicism and level of education, and professional seniority. There was no significant association between organizational cynicism and marital status. From this study, it was found that the independent variable, which had the highest predictive value for organizational cynicism, was social connectedness followed by gratitude, and the variable group with the lowest predictive value was found to be demographic variables.
Keywords: Eğitim; Eğitim Araştırmaları